Multidisciplinary, biopsychosocial factors contributing to return to running and running related stress urinary incontinence in postpartum women. Issue 22 (18th June 2021) - Moore, Isabel S; James, Megan L; Brockwell, Emma; Perkins, Joanna; Jones, Alex L; Donnelly, Gráinne M
Abstract : Objectives: To examine contributory factors behind postpartum return-to-running and return to pre-pregnancy running level, in addition to risk factors for postpartum running-related stress urinary incontinence (SUI). Methods: 881 postpartum women completed an online questionnaire. Clinically and empirically derived questions were created relating to running experiences and multidisciplinary, biopsychosocial contributory factors. Logistic regression was used to determine predictors for return-to-running, returning to pre-pregnancy level of running and running-related SUI. Results: Median time to first postpartum run was 12 weeks. Running during pregnancy (OR: 2.81 (1.90 to 4.15)), a high weekly running volume (OR: 1.79 (1.22 to 2.63)), lower fear of movement (OR: 0.53 (0.43 to 0.64)) and not suffering vaginal heaviness (OR: 0.52 (0.35–0.76)) increased the odds of return-to-running. Factors that increased the odds of returning to pre-pregnancy running level were a low weekly running volume (OR: 0.38 (0.26 to 0.56)), having more than one child (OR: 2.09 (1.43 to 3.05)), lower fear of movement (OR: 0.78 (0.65 to 0.94)), being younger (OR: 0.79 (0.65 to 0.96)) and shorter time to running after childbirth (OR: 0.74 (0.60 to 0.90)). Risk factors for running-related SUI were having returned to running (OR: 2.70 (1.51 to 4.76)) and suffering running-related SUI pre-pregnancy (OR: 4.01 (2.05 to 7.82)) and during pregnancy (OR: 4.49 (2.86 to 7.06)); having a caesarean delivery decreased the odds (OR: 0.39 (0.23 to 0.65)). Conclusion: Running during pregnancy may assist women safely return-to-running postpartum. Fear of movement, the sensation of vaginal heaviness and running-related SUI before or during pregnancy should be addressed early by healthcare providers.